A multimethod dating study of ancient permafrost, Batagay megaslump, east Siberia. (January 2022) - Murton, Julian B.; Opel, Thomas; Toms, Phillip; Blinov, Alexander; Fuchs, Margret; Wood, Jamie; Gärtner, Andreas; Merchel, Silke; Rugel, Georg; Savvinov, Grigoriy; Wetterich, Sebastian
Abstract: Dating of ancient permafrost is essential for understanding long-term permafrost stability and interpreting palaeoenvironmental conditions but presents substantial challenges to geochronology. Here, we apply four methods to permafrost from the megaslump at Batagay, east Siberia: (1) optically stimulated luminescence (OSL) dating of quartz, (2) post-infrared infrared-stimulated luminescence (pIRIR) dating of K-feldspar, (3) radiocarbon dating of organic material, and (4) 36 Cl/Cl dating of ice wedges. All four chronometers produce stratigraphically consistent and comparable ages. However, OSL appears to date Marine Isotope Stage (MIS) 3 to MIS 2 deposits more reliably than pIRIR, whereas the latter is more consistent with 36 Cl/Cl ages for older deposits. The lower ice complex developed at least 650 ka, potentially during MIS 16, and represents the oldest dated permafrost in western Beringia and the second-oldest known ice in the Northern Hemisphere. It has survived multiple interglaciations, including the super-interglaciation MIS 11c, though a thaw unconformity and erosional surface indicate at least one episode of permafrost thaw and erosion occurred sometime between MIS 16 and 6. The upper ice complex formed from at least 60 to 30 ka during late MIS 4 to 3. The sand unit above the upper ice complex is dated to MIS 3–2, whereas the sand unit below formed at some time between MIS 4 and 16.